Phenylated Benzotetraphenes (Dibenzanthracenes) by Nickel-Catalyzed Diphenylacetylene Cycloadditions to Linear [3]Phenylenes - Gu, Zhenhua; Vollhardt, K. Peter C. (Synthesis, 2013)
Ni(COD)(PMe3)2 catalyzes the cycloaddition of diphenylacetylene to the four-membered rings of linear [3]phenylene and its 2,3,7,8-tetrakis(trimethylsilyl) derivative. The reaction proceeds via initial formation of the 5,6-diphenylbenzo[3,4]cyclobuta[1,2-b]phenanthrene frame, followed by a competitive second, nonregioselective alkyne insertion to furnish the corresponding phenyl-substituted benzo[k]- and -[m]tetraphenes.
Keywords: alkynes; arenes; cycloaddition; nickel; polycycles